2004
DOI: 10.1258/0022215042244750
|View full text |Cite
|
Sign up to set email alerts
|

Metastasizing mixed tumour of the parotid gland presenting as multiple lung metastases

Abstract: Metastasis is a feature of malignant neoplasms. Although rare, metastasizing pathologically benign mixed tumour has been reported. This report describes a 33-year-old woman with multiple lung metastases from mixed tumour. A small preauricular mass had been removed 23 years earlier. Six years later, the patient had the same symptom; the recurrent mass was resected. She was not aware of the exact pathological diagnosis of the previous tumours. One of the most common features of metastasizing mixed tumour is recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…It has been suggested that metastasising tumours have a higher mitotic rate than non-recurring lesions, but this theory is not universally accepted and this feature was not seen in our patient (6)(7)(8)(9). The Patients (81%) with MPA have a history of at least one local recurrence of PA prior to the detection of distant metastasis of the tumour at the primary site is a characteristic feature of these metastasising pleomorphic adenomas; recurrence ocurring in about 90% of cases (5). There is often a long interval between the diagnosis of the primary mixed tumour and the metastasis (5,6).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…It has been suggested that metastasising tumours have a higher mitotic rate than non-recurring lesions, but this theory is not universally accepted and this feature was not seen in our patient (6)(7)(8)(9). The Patients (81%) with MPA have a history of at least one local recurrence of PA prior to the detection of distant metastasis of the tumour at the primary site is a characteristic feature of these metastasising pleomorphic adenomas; recurrence ocurring in about 90% of cases (5). There is often a long interval between the diagnosis of the primary mixed tumour and the metastasis (5,6).…”
Section: Discussionmentioning
confidence: 58%
“…Benign MPA is distinguished from truly malignant pleomorphic tumors (such as carcinomas arising from pleomorphic adenomas, and carcinosarcomas) by its benign histologic features. However, there are no agreed histopathologic parameters that can differentiate a non-metastatic pleomorphic adenoma from Mpa (4,5,8). It has been suggested that metastasising tumours have a higher mitotic rate than non-recurring lesions, but this theory is not universally accepted and this feature was not seen in our patient (6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some cases have presented to non-head and neck clinicians with distant metastases located in the kidney and lung and have been considered a malignant process, until FNAC or excision have proven pleomorphic adenoma metastases; only then had it transpired, on history or examination, that the patients had concurrently or previously had a salivary gland pleomorphic adenoma removed [13,15].…”
Section: Modes Of Presentationsmentioning
confidence: 99%